2017
DOI: 10.1177/1971400917712268
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial dural chondroma in a child—conventional and advanced neuroimaging characteristics and differential diagnosis

Abstract: Intracranial chondromas are rare tumors, especially in the pediatric population. We describe the conventional and advanced neuroimaging characteristics of this rare convexity dura-based chondroma in a young adolescent. In particular we demonstrate that diffusion-weighted imaging (DWI) facilitates differentiation between a dura-based chondroma and the more frequent classical meningioma. Chondromas are typically DWI hypointense with high apparent diffusion coefficient (ADC) values while meningiomas are typically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…In this study, we report the case of a 38-year-old man. The clinical presentation of intracranial chondromas depends on their location and includes headache, seizures, and focal neurologic deficits [6,7].…”
Section: Discussionmentioning
confidence: 99%

Intracranial Dural Chondroma: Case Report and Review of Literature

Napoleao IMBUNHE,
Yao Christian Hugues DOKPONOU,
Fresnel Lutece Ontsi OBAME
et al. 2023
World J. Adv. Res. Rev.
“…In this study, we report the case of a 38-year-old man. The clinical presentation of intracranial chondromas depends on their location and includes headache, seizures, and focal neurologic deficits [6,7].…”
Section: Discussionmentioning
confidence: 99%

Intracranial Dural Chondroma: Case Report and Review of Literature

Napoleao IMBUNHE,
Yao Christian Hugues DOKPONOU,
Fresnel Lutece Ontsi OBAME
et al. 2023
World J. Adv. Res. Rev.
“…Due to the slow growth of chondromas, no peritumoral edema appears on MRI. It has also been reported that the cartilage matrix in chondroma can lead to its low signal on diffusion-weighted imaging (DWI), and the arrangement of cells in the lesion shows the apparent diffusion coefficient ( 19 , 20 ). The imaging characteristics, including the “snowman” shape of pituitary tumor, “dural tail sign” of meningioma, vascular lumen and thrombus of cavernous hemangioma, and eggshell calcification of craniopharyngioma, could distinguish ICDs from other tumors ( 21 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Angiograms show that CDCs are nonvascular tumors [ 9 , 47 ]. In addition, CDCs are typically DWI hypointense with high ADC (apparent diffusion coefficient) values [ 12 , 16 ].…”
Section: Discussionmentioning
confidence: 99%